2018
DOI: 10.3390/en11123256
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Residual Stress Analysis of Soldering and Lamination Processes for Fabrication of Crystalline Silicon Photovoltaic Modules

Abstract: In this study, we developed a finite element model to assess the residual stress in the soldering and lamination processes during the fabrication of crystalline silicon (Si) photovoltaic (PV) modules. We found that Si wafers experience maximum thermo-mechanical stress during the soldering process. Then, the Si solar cells experience pressure during the process of lamination of each layer of the PV module. Thus, it is important to decrease the residual stress during soldering of thin Si wafers. The residual str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…7) Chen et al 8) reported that the increasing soldering temperature causes bow and residual stress increase, and increasing residual stress may cause damage in the region of the wafer near the electrode. Also, it was concluded by Shin et al 9) that Si wafers experience maximum thermomechanical stress during the soldering process. Then, the Si solar cells experience pressure during the process of lamination of each layer of the PV module.…”
Section: Nickel Micro-plating Bonding (Nmpb)mentioning
confidence: 99%
“…7) Chen et al 8) reported that the increasing soldering temperature causes bow and residual stress increase, and increasing residual stress may cause damage in the region of the wafer near the electrode. Also, it was concluded by Shin et al 9) that Si wafers experience maximum thermomechanical stress during the soldering process. Then, the Si solar cells experience pressure during the process of lamination of each layer of the PV module.…”
Section: Nickel Micro-plating Bonding (Nmpb)mentioning
confidence: 99%
“…Such as Europe: 1.2-1.4 times; the United States and India: > 1.4 times; Japan: 2 times. Appropriate ratio of DC/AC can increase the economical cost of the entire PV power station and reduce LCOE [31]- [33].…”
Section: Pv System Technologymentioning
confidence: 99%
“…Surface bonding is an essential step in device manufacturing and assembly, providing mechanical support, heat transfer, and electrical integration. Traditional surface bonding techniques in electronic assembly strongly rely on high-temperature processes such as reflow soldering, which can lead to undesirable thermal damage, toxic solder materials pollution, and residual stress at the bonding interface [ 1 , 2 ]. Besides, thermo-compression is another widely used bonding approach because it provides intrinsic interconnections and excellent bonding strength.…”
Section: Introductionmentioning
confidence: 99%